Metamaterials: Fundamentals and Applications III 2010
DOI: 10.1117/12.860584
|View full text |Cite
|
Sign up to set email alerts
|

On the nanoscale transmission of quantum angular momentum

Abstract: The electromagnetic propagation of angular momentum associated with photon spin has evolved into a subject of much broader remit, following the theoretical and experimental realization of optical beams that can convey quantized orbital angular momentum. The possibility of transmitting such information over nanoscale distances raises numerous issues. For example, it is known that electron spin can be relayed by near-field communication between exciton states in quantum dot assemblies; the question arises, can o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Such a phenomenon would, indeed, be consistent with the effects of rotating optical elements. [34] It is also interesting to reflect on certain similarities of feature in the resonance transfer of energy between spin-selected states in quantum dots, [35] a congruence that arises from the quantum amplitude for each process involving a term of identical mathematical structure to the factor cast in square brackets in equation (11). It has been shown that the quantum dot spin and energy transfer process provides for a complete fidelity of spin transmission only in cases where the initial electron spin is aligned, parallel or anti-parallel, with the pair displacement vector.…”
Section: Resultsmentioning
confidence: 99%
“…Such a phenomenon would, indeed, be consistent with the effects of rotating optical elements. [34] It is also interesting to reflect on certain similarities of feature in the resonance transfer of energy between spin-selected states in quantum dots, [35] a congruence that arises from the quantum amplitude for each process involving a term of identical mathematical structure to the factor cast in square brackets in equation (11). It has been shown that the quantum dot spin and energy transfer process provides for a complete fidelity of spin transmission only in cases where the initial electron spin is aligned, parallel or anti-parallel, with the pair displacement vector.…”
Section: Resultsmentioning
confidence: 99%
“…On this well-established basis the present analysis aims to deliver a construct that is entirely rigorous, robust and well suited for describing the interpretable transmission of quantum optical angular momentum. Developing and expanding on the approach of a preliminary study [38] communicated in a recent conference, the theory identifies the effects and limitations imposed by scattering in any material medium, eliciting new physical insights into the underlying photonics.…”
Section: Introductionmentioning
confidence: 99%